Assessment of the psychological state of children with dental anomalies - A. V. Razilova; Ad. A. Mamedov; A. V. Simonova (Неврология, нейропсихиатрия, психосоматика)
Currently, a significant proportion of children have dental anomalies (DA) and require orthodontic treatment. The effectiveness of treatment is reduced due to the age-related characteristics of the child's psyche, which lengthens the time and affects the quality of the appointment.Objective: to assess the emotional state of children with DA aged 6–12 years.Patients and methods. To study the characteristics of the psychological state of children, 122 patients aged 6–12 years (44 boys and 78 girls, mean age 9 [7; 11] years) were examined and orthodontically treated. Children's complaints, the presence of tics and obsessive habits were assessed. The psychological state of the patients was assessed using the G.P. Lavrentieva and T.M. Titarenko anxiety level in children questionnaire. Causes and factors that increase anxiety at the reception were assessed using a questionnaire developed by the authors.Results and discussion. Aesthetic defect and speech disorders were the most frequent complaints among children aged 6–12 years with DA (58 and 23%, respectively), especially among older girls (r=0.72). 91.2% of children had obsessive habits, 48% had motor tics. Three groups were distinguished: with low (59.0%), medium (19.7%) and high (21.3%) levels of anxiety. No significant associations were found between the anxiety level and gender, age, presence of tics and obsessive habits. Factors that increased anxiety in children during an orthodontist's appointment were: past personal negative experience at a dental appointment (in 27.0%); office environment (23.8%); negative experience of parents or peers (16.4%); frequent visits to medical institutions in the past (21.3%); family relations (11.5%). The most common anxiety causes were pain expectation and inexplicable fear, a little less often - unpleasant manipulations in the oral cavity and comments from the parent. The rarest cause of anxiety was a disapproving remark from an orthodontist.Conclusion. Children with DA aged 6–12 years have an increased anxiety level, independent of gender and age. These children require a special approach from the orthodontist and, possibly, a consultation with a psychotherapist.